2019
DOI: 10.1016/j.jpag.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Ovotesticular Disorders of Sex Development: Improvement in Spermatogonia after Removal of Ovary and Müllerian Structures

Abstract: Background: Ovotesticular disorders of sex development is a condition defined as the presence of ovarian tissue containing ovarian follicles and testicular tissue containing seminiferous tubules in the same individual. Case: We report on a 19-year-old who is phenotypically male, with a 46,XX/46,XY mosaicism karyotype, who presented later in life with cyclical abdominal pain that resembled menstrual cramps and unilateral undescended testes. Summary and Conclusion: He underwent laparoscopic hysterectomy and righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…5.1.4. 45,XX/46,XY 45,XX/46,XY DSD may arise as a result of mosaicism or true chimerism [21,143]. Phenotypes range from typical male to typical female.…”
Section: X/46xymentioning
confidence: 99%
See 1 more Smart Citation
“…5.1.4. 45,XX/46,XY 45,XX/46,XY DSD may arise as a result of mosaicism or true chimerism [21,143]. Phenotypes range from typical male to typical female.…”
Section: X/46xymentioning
confidence: 99%
“…In phenotypic females, spontaneous pregnancies have been reported [144]. For males, azoospermia is considered almost universal, although there are reports of successful TESE and subsequent pregnancies using the cryopreserved sperm [145,146] and a case of an azoospermic male whose sperm count became normal after Mullerian structures had been removed [143]. These cases indicated that fertility preservation may be possible in some 46,XX/46,XY individuals using semen cryopreservation or TESE.…”
Section: X/46xymentioning
confidence: 99%
“…4 Ovotesticular DSD Ovotesticular DSD, earlier referred to as true hermaphroditism, is a rare form of DSD, with an incidence of 1 per 100,000 live births. 12 Genetically, majority of these individuals are 46XX with other less common karyotypes including 46,XX/XY mosaicism and rarely 46XY. 12,13 This disorder is characterized by presence of ovarian tissue with primordial follicles and testicular tissues with seminiferous tubules, within the same individual.…”
Section: Urogenital Sinusmentioning
confidence: 99%
“…12 Genetically, majority of these individuals are 46XX with other less common karyotypes including 46,XX/XY mosaicism and rarely 46XY. 12,13 This disorder is characterized by presence of ovarian tissue with primordial follicles and testicular tissues with seminiferous tubules, within the same individual. Clinical features, which depend on karyotype, can vary from genital ambiguity, cryptorchidism, gynecomastia, and cyclical hematuria.…”
Section: Urogenital Sinusmentioning
confidence: 99%